(untitled) (Research, Society and Development, 2020)
The World Health Organization (WHO), the United Nations International Children’s Emergency Fund (UNICEF) and the Ministry of Health, recommend that breastfeeding be up to 6 months of age. After this period, complementary feeding should be added, and breast milk shoul continue until two years of age. This is explained by the fact that human milk provides protection to the babies against pathogens, being a strong ally in building their immunity. Thus, the present study aims to show the importance of breastfeeding in the construction of the infant’s immune system, specifically in innate immunity, as well as also to describe the consequences that early weaning can cause the newborn’s health. This study is a bibliographic review, with a qualitative approach, of an exploratory type. Because breast milk has necessary components for the development of the newborn, breastfeeding is essential in building the newborn’s immunity, especially in the innate, and early weaning should therefore be avoided.